On some analogies between one-criterion decision making under uncertainty and multi-criteria decision making under certainty - Gaspars-Wieloch, Helena (Economics and Business Review, 2021)
One-criterion decision making under uncertainty (1-DM/U) is related to situations in which the decision maker (DM) evaluates the alternatives on the basis of one objective, but e.g. due to numerous uncertain future factors some parameters of the problem are not deterministic. Instead of entirely known paramaters, a set of possible scenarios is available. Multi-criteria decision making under certainty (M-DM/C) concerns cases where the DM assesses particular options in terms of many objectives. The parameters are known. Therefore, scenario planning is redundant. Both issues are investigated by many researchers and practitioners, since real economic decision problems are usually at least uncertain or multi-objective. In the paper, numerous analogies between 1-DM/U and M-DM/C are revealed. Some of them have existed for many decades, but others, so far, have not been developed. A careful examination of all the similarities enables an improvement of existing methods and a formulation of new algorithms for 1-DM/U and M-DM/C. The article presents six pairs of similar procedures and contains the description of three novel approaches created by analogy to existing ones.